Staying at home : between care, (social) housing and health care - Marion Ille-Roussel (GéoProximitéS)
Staying at home is a central concept of ageing policies that describes the ability to age in an independent dwelling, as opposed to living and being taken care of in a nursing home. Staying at home is facilitated by physical adaptation of the building, technical support and/or the help of people. Staying at home is made possible by the participation of various stakeholders as parts of the (social) housing sector, home-care sector and health care system. As we show in this article, those sectors are coming closer and may overlap. Social housing providers in France, the UK and Germany participate in the definition of staying at home as housing stakeholders who plan to continue building and managing housing. They defend a vision of housing as support for (home)care and care. Social landlords do not develop homecare and health care services but may offer social support before or in addition to homecare. Dwelling’s adaptation should allow people to stay at home, but also facilitate the activities of caregivers. The support of inhabitants by other stakeholders is made possible by the activities as builders and housing managers of social housing organizations. Housing defines homecare and frames the space of care.